2020
DOI: 10.3991/ijet.v15i12.13455
|View full text |Cite
|
Sign up to set email alerts
|

Mining Smart Learning Analytics Data Using Ensemble Classifiers

Abstract: Recent progress in technology has altered the learning behaviors of students; besides giving a new impulse which reshapes the education itself. It can easily be said that the improvements in technologies empower students to learn more efficiently, effectively and contentedly. Smart Learning (SL) despite not being a new concept describing learning methods in the digital age- has caught attention of researchers. Smart Learning Analytics (SLA) provides students of all ages with research-proven frameworks, helping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Existing literatures have explored the ensemble methods in education issues. Kausar et al [12] utilized the ensemble methods to analyze the students' learning performance, and demonstrated that the ensemble methods of bagging and stacking classifiers can enhance the classification performance. Sun et al [13] proposed a multi-classification model, by combining the feature integration and the ensemble method to predict the education grants of students.…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…Existing literatures have explored the ensemble methods in education issues. Kausar et al [12] utilized the ensemble methods to analyze the students' learning performance, and demonstrated that the ensemble methods of bagging and stacking classifiers can enhance the classification performance. Sun et al [13] proposed a multi-classification model, by combining the feature integration and the ensemble method to predict the education grants of students.…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…Ghosh et al [34] made use of lazy algorithms to identify the student vulnerable of failing mathematics courses and forward the information to the corresponding instructors. Kausar et al [35] made use of ensemble techniques to examine the relationship between students' semester course and final results. Hussain et al [36] concludes decision tree as a robust solution in successfully recognizing the students who truly exhibit low-engagement during assessment activities.…”
Section: Machine Learningmentioning
confidence: 99%
“…Kausar et al [25] applied ensemble techniques over a dataset to examine the relationship between students' features such as quizzes, assignment, exams marks and the final results. The experimental evaluation concludes Random Forest and Stacking classifiers with achieving accuracies of 77% and 78% respectively prevailing K-NN and Naïve bayes classifiers.…”
Section: Literature Reviewmentioning
confidence: 99%